Islamic Education Management Model for Integrating Tahfizh and Vocational Education at Maahad Tahfiz - Syafiul Anam; Ita Nurmalasari (Al-Qalam Institue, 2026)
The integration of tahfizh and vocational education has become a strategic approach for Islamic educational institutions to enhance graduates’ relevance and economic independence. This study aims to analyze the Islamic education management model implemented at Maahad Tahfizh Vokasional Aman Bistari (MTVAB) in Malaysia, recognized as the first institution to formally integrate Qur’anic memorization with vocational training. This research employs a library research method using a descriptive qualitative approach. Data were analyzed by examining curriculum integration, managerial mechanisms, and external collaboration models adopted by the institution. The findings indicate that MTVAB’s effectiveness is supported by integrative curriculum planning, systematic supervision, and strategic partnerships with industries and professional certification bodies. These elements enable the institution to balance spiritual development with vocational competence. The study implies that an integrative management model can serve as a viable reference for Islamic educational institutions seeking to produce graduates who are spiritually grounded, professionally skilled, and economically independent in contemporary society